2013
DOI: 10.3348/kjr.2013.14.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Application of31P MR Spectroscopy to the Brain Tumors

Abstract: ObjectiveTo evaluate the clinical feasibility and obtain useful parameters of 31P magnetic resonance spectroscopy (MRS) study for making the differential diagnosis of brain tumors.Materials and MethodsTwenty-eight patients with brain tumorous lesions (22 cases of brain tumor and 6 cases of abscess) and 11 normal volunteers were included. The patients were classified into the astrocytoma group, lymphoma group, metastasis group and the abscess group. We obtained the intracellular pH and the metabolite ratios of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
67
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 25 publications
11
67
1
4
Order By: Relevance
“…However, we did not find statistically significant difference in PME/PDE ratio in any of the group. Previous studies have found significantly high PME/PDE ratio in astrocytoma, metastases and lymphoma compared to controls [13]. But these findings are variable and have limitations as previous studies had also shown increase in both PME and PDE in most tumours , proliferating tissues like regenerating liver, benign tumours and embryo [5].…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…However, we did not find statistically significant difference in PME/PDE ratio in any of the group. Previous studies have found significantly high PME/PDE ratio in astrocytoma, metastases and lymphoma compared to controls [13]. But these findings are variable and have limitations as previous studies had also shown increase in both PME and PDE in most tumours , proliferating tissues like regenerating liver, benign tumours and embryo [5].…”
mentioning
confidence: 62%
“…The phosphate metabolites imaged are probably intracellular as the extra cellular concentration of these metabolites is negligible [12]. The integral values obtained of each metabolites are not absolute but relative [4] and thus various metabolite ratios are used like PME/ PDE, PDE/ATP, PCr/ATP etc in various studies [5,13].…”
mentioning
confidence: 99%
“…Their examination would require extraction of the membrane and the application of organic solvents, which would allow to distinguish at least the major human brain phospholipids including phosphatidylcholine, phosphatidylserine, sphingomyelin, phosphatidylinositol, and phosphatidylethanolamine (Garett and Grisham 2008;Kornienko and Pronin 2009). However, it is possible to spectroscopically measure precursors of their synthesis and products of their degradation as the tCho signal contributors (Solivera and Law 2009;Ha et al 2013). Since the level of tCho particularly reflects the concentration of phosphocholine which is more than twice increased in highgrade gliomas (Lupo et al 2007;McKnight and Wladman 2010), tCho is suitable for monitoring tumor carcinogenesis (Guillevin et al 2008;Housni and Boujraf 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Membrane phospholipids are beneficial for spectroscopic tumor detection. They perform important function as intracellular second messengers involved in the regulation of cell differentiation and proliferation (Wijnen 2010;Ha et al 2013). Unfortunately, using the in vivo 1 H MRS it is not possible to directly evaluate these phospholipids due to their incorporation in the cell membranes (Soares and Law 2009;Barker 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation